2019
DOI: 10.35845/kmuj.2019.19114
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol Attenuates Oxidative Stress in Chemotherapy Induced Acute Kidney Injury: An Experimental Rat Model

Abstract: OBJECTIVE:To investigate the anti-oxidative and anti-nephrotoxic effects of resveratrol in cisplatin induced nephrotoxic albino Wistar rats. METHODS:This quasi-experimental study was performed at Isra University, Hyderabad, Pakistan. Thirty male albino Wistar rats were divided into three g r o u p s : g r o u p -A ( c o n t r o l ) , g r o u p -B ( c i s p l a t i n ) a n d g r o u p -C (cisplatin+resveratrol). Biochemical [serum urea, creatinine and glutathione peroxidase (GPX)] and renal histomorphology was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 7 publications
1
3
0
Order By: Relevance
“…17 In our experiment, administration of cisplatin was followed by a reduction in the weight of the experimental animals, which is consistent with previous findings. 3 The animals receiving Larginine therapy showed a much less reduction in their weights, which is consistent with the findings of Eshraghi-Jazi et al, who observed that arginine ameliorates cisplatin-induced weight loss in male rats. 18 In this study, there was an increase in the blood urea and creatinine of all the animals receiving cisplatin as compared with the controls.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…17 In our experiment, administration of cisplatin was followed by a reduction in the weight of the experimental animals, which is consistent with previous findings. 3 The animals receiving Larginine therapy showed a much less reduction in their weights, which is consistent with the findings of Eshraghi-Jazi et al, who observed that arginine ameliorates cisplatin-induced weight loss in male rats. 18 In this study, there was an increase in the blood urea and creatinine of all the animals receiving cisplatin as compared with the controls.…”
Section: Discussionsupporting
confidence: 90%
“…16 In our study, histological examination of the kidneys showed clear evidence of cisplatin-induced nephrotoxic injury manifested as marked tubular cell necrosis, vascular congestion, and tubular dilatation, which is consistent with previous findings. 3 However, these changes were much less evident in the arginine treated animals. These findings are consistent with the findings of Başhan and coworkers, who noted that histopathological changes were reversed in the nephrotoxic animals who received L-arginine as well.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…nephroprotective [20], antiinflammatory [21], antidepressant and antioxidant properties [22][23][24]and effects of immunity enhancers W Egyptian Journal of Veterinary Sciences https://ejvs.journals.ekb.eg/ Egypt. J. Vet.…”
Section: Resveratrolmentioning
confidence: 99%